2000
DOI: 10.1021/jm9903139
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Gag Pentapeptide Analogue that Binds Human Cyclophilin A More Efficiently than the Entire Capsid Protein:  New Insights for the Development of Novel Anti-HIV-1 Drugs

Abstract: Cyclophilin A (hCyp-18), a ubiquitous cytoplasmic peptidyl-prolyl cis/trans isomerase (PPIase), orchestrates HIV-1 core packaging. hCyp-18, incorporated into the virion, enables core uncoating and RNA release and consequently plays a critical role in the viral replication process. hCyp-18 specifically interacts with a single exposed loop of the Gag polyprotein capsid domain via a network of nine hydrogen bonds which mainly implicates a 7-mer fragment of the loop. As previously reported, the corresponding linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 64 publications
3
51
0
Order By: Relevance
“…We also found that these substitutions reduced CypA incorporation into virions (Fig. 3C), which is compatible with previous reports by two groups (28,29). It was therefore postulated that MT-2 and H9 cells contained high CypA amounts, thereby compromising HIV-1 WT replication.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that these substitutions reduced CypA incorporation into virions (Fig. 3C), which is compatible with previous reports by two groups (28,29). It was therefore postulated that MT-2 and H9 cells contained high CypA amounts, thereby compromising HIV-1 WT replication.…”
Section: Discussionsupporting
confidence: 92%
“…Complexation yields varied only slightly upon addition of recombinant hCyp-18 (final concentration: 64 mm), [9] except in the case of complex 4 i, which was formed more efficiently when cyclophilin was added to the mixture (Figure 2 A, graphs a and b), an effect that we called the "cyclophilin-enhancing effect". As expected, all complexes readily dissociated upon addition of GSH in the absence of hCyp-18 (Figures 2 B and D, graph d).…”
Section: Resultsmentioning
confidence: 99%
“…However, inhibitors of CypA are mainly derived from the nature sources (such as CsA [2], FK506 [10], rapamycin [11], and sanglifehrin A [12]) and peptide analogs [13], which are all structural complex molecules, and little has been reported regarding the small molecule CypA inhibitors. Recently, using a strategy integrating focused combinatorial library design, virtual screening, chemical synthesis, and bioassay, we have designed and synthesized several series of novel small molecular CypA inhibitors, 17 of which showed PPIase inhibitory activities with IC 50 values at micromolar level [14 -17].…”
mentioning
confidence: 99%